DELINEATION OF SUBSIDENCE IN THE ALTERATION ZONE IN ULUBELU GEOTHERMAL FIELD BASED ON INTERFEROMETRY SYNTHETIC APERTURE RADAR TIME SERIES - Ahmad Zaenudin; Ilham Tri Putra Sofiyadin; Rachmat Arief (Engineering Faculty Universitas Lampung, 2020)
Ulubelu is a geothermal region managed by Pertamina Geothermal Energy (PGE) located in Mount Kukusan, Sula, Kabawok, Kuripan and Rindingan. The learning of subsidence is required for disaster mitigation. This research use 33 SAR data of Sentinel1-A which bundled for generate an APS and then using multi temporal analysis to generate InSAR time series from 2018 September to 2017 April. InSAR time series can detect indication of subsidence practically and quickly. Decrease velocity of subsidence in the Ulubelu geothermal region is an average of 3,3 mm/yr (X=453.558, Y=9.412.437, 48 S zone. This subsidence is domination by altered rocks compaction. In the other hand, the geological structure (faults) and lithology also surface loading affected the subsidence. Pekon Gn. Tiga, Karang Rejo, Muara Dua and Pagar Alam are the worst of subsidence area. Mitigation must to be clear early for areas that have the worst subsidence in Ulubelu geothermal field.